International Economics - Gerber, James (Pearson, 2024)
A principles-level introduction that’s accessible to students of allmajors, International Economics uses real-lifeapplications to cover both the macro and micro components of internationaleconomics. The text illuminates economic institutions and policies,as well as recent developments in the global economy, without requiring the useof higher-level math.